The role of state among the essential values of the Maqāṣid Al-Sharī‘Ah ın skeleton metaphor - Kayadibi, Saim (2018)
Muslim scholars have mainly considered the maqāṣid al-sharī‘ah within three categories: ḍarūriyyāt (the essentials), ḥājiyyāt (the complementaries) and tahsīniyyāt (the desirables or the embellishments). The concept of maṣlaḥah is meant to protect the maqāṣid al-sharī‘ah (the higher objectives of Sharī‘ah), which consist of seven essential values, namely, religion, life, intellect, lineage, wealth, honour and state, all of which promote the people’s welfare and prevent all kind of evils. They are considered essentials because neglecting them would cause total social disruption and anarchy. Despite the fact that classical scholars considered the darūriyyāt to be six in number, this researcher suggests that the value of “state” be added to this list. These values must be upheld and protected from any real or unexpected threat either by maintaining the essentials or removing the disruption. The concept of state is just as essential as the other six values, for without it all of them would be endangered and considered incomplete. Therefore, as a value the “state” guarantees the continued existence of the other values. The objective of this study is to highlight the significant role of the seventh value in the essential values of the maqāṣid al-sharī‘ah. Since it is a conceptual paper, content analysis research method is used by collecting data from library and secondary resources. This paper, therefore, intended to contribute to the academic research related to the maqāṣid al-sharī‘ah by identifying the seventh value of the maqāṣid al-sharī‘ah by developing skeleton metaphor that combines all values in order to achieve successful maqāṣid al-sharī‘ah practice in the Muslim world.